Hadezhnost' rezheniya dvigatel'nykh zadach - Korenberg, V. B. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this lecture was to display the problem of the reliability in motor tasks' working on. The author characterises the various aspects in the concept "reliability". He discusses the problem of the reliability in motor tasks working on from the positions of its hierarchical structure; the concept the goal back-drop motor function of a body; the problem of risk in motor activity; the other key concepts of the examined problem. The classification of the sports motor skills is offered. The ways of reliability in motor actions' increase in sportscompetitions are marked.